Conformation-Dependent Hydrogen-Bonding Interactions in a Switchable Artificial Metalloprotein - Fatima, Saman; Mehrafrooz, Behzad; Boggs, David G.; Ali, Noor; Singh, Swapnil; Thielges, Megan C.; Bridwell-Rabb, Jennifer; Aksimentiev, Aleksei; Olshansky, Lisa (Biochemistry, 2024)
Hydrogen-bonding (H-bonding) interactions in metalloprotein active sites can critically regulate enzyme function. Changes in the protein structure triggered by interplay with substrates, products, and partner proteins are often translated to the metallocofactor by way of specific changes in H-bond networks connected to the active site. However, the complexities of metalloprotein architecture and mechanism often preclude our ability to define the precise molecular interactions giving rise to these intricate regulatory pathways. To address this shortcoming, we have developed conformationally switchable artificial metalloproteins (swArMs) in which allosteric Gln-binding triggers protein conformational changes that impact the microenvironment surrounding an installed metallocofactor. Herein, we report a combined structural, spectroscopic, and computational approach to enhance the conformation-dependent changes in H-bond interactions surrounding the metallocofactor site of a swArM. Structure-informed molecular dynamics simulations were employed to predict point mutations that could enhance active site H-bond interactions preferentially in the Gln-bound holo-conformation of the swArM. Testing our predictions via the unique infrared spectral signals associated with the metallocofactor site, we have identified three key residues capable of imparting conformational control over the metallocofactor microenvironment. The resultant swArMs not only model biologically relevant structural regulation but also provide an enhanced Gln-responsive biological probe to be leveraged in future biosensing applications.